Red Pine Bark Extract Alleviates Akt/GSK-3β Signaling Disruption in the Hippocampus of Streptozotocin-Induced Diabetic Sprague-Dawley Rats - Kim, Kwan Joong; Akhmedova, Zukhra; Heo, Ho Jin; Kim, Dae-Ok (Journal of microbiology and biotechnology, 2024)
This study investigates whether red pine ( Sieb. et Zucc.) bark extract (PBE) can alleviate diabetes and abnormal apoptosis signaling pathways in the hippocampus of streptozotocin (STZ)-induced diabetic Sprague-Dawley (SD) rats. Two dosages of PBE (15 and 30 mg/kg of body weight/day) were administered orally to STZ-induced diabetic SD rats for 20 days. Blood glucose level and body weight were measured once per week. After 20 days of oral administration of PBE, the rat hippocampus was collected, and the production of Akt, -Akt, GSK-3β, -GSK-3β, tau, -tau, Bax, and Bcl-2 proteins were determined by western blot analysis. A decrease in blood glucose level and recovery of body weight were observed in PBE-treated diabetic rats. In the Akt/GSK-3β/tau signaling pathway, PBE inhibited diabetes-induced Akt inactivation, GSK-3β inactivation, and tau hyperphosphorylation. The protein production ratio of Bax/Bcl-2 was restored to the control group level. These results suggest that PBE, rich in phenolic compounds, can be used as a functional food ingredient to ameliorate neuronal apoptosis in diabetes mellitus.